2013
DOI: 10.1186/1745-6215-14-247
|View full text |Cite
|
Sign up to set email alerts
|

Consent, including advanced consent, of older adults to research in care homes: a qualitative study of stakeholders’ views in South Wales

Abstract: BackgroundCare home residents, especially those lacking capacity to provide consent for themselves, are frequently excluded from research, thus limiting generalisability of study findings. We set out to explore stakeholders’ views about the ethical and practical challenges associated with recruiting care home residents into research studies.MethodsQualitative individual interviews with care home residents (n = 14), their relatives (n = 14), and general practitioners (GPs) (n = 10), and focus groups (n = 2) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 21 publications
(22 reference statements)
0
40
0
1
Order By: Relevance
“…Compared with ageing research overall, research in long-term care remains relatively underdeveloped [9]. However, the recruitment of vulnerable older adults to research has reported low refusal rates, suggesting their willingness to be involved when given the opportunity [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with ageing research overall, research in long-term care remains relatively underdeveloped [9]. However, the recruitment of vulnerable older adults to research has reported low refusal rates, suggesting their willingness to be involved when given the opportunity [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Both the MCA and CTR require a decision based on what the person lacking capacity would have wanted, had they the capacity to choose for themselves, as their presumed will. The complexity of the current legal framework, its legislative differences and uncertainty surrounding their interpretation has resulted in confusion both for researchers and Research Ethics Committees,5 6 as well as clinicians, relatives and carers involved in decisions about adults lacking capacity participating in research 7. These differences increase the burden on those involved in making decisions about research participation and present barriers to conducting research with individuals with cognitive impairments 8 9.…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of the current legal framework, its legislative differences, and uncertainty surrounding their interpretation, has resulted in confusion both for researchers and Research Ethics Committees [11], as well as clinicians, relatives, and carers involved in decisions about people participating in research [7]. This issue remains one to be addressed and, unless it is done so, strategies introduced to improve the inclusion of vulnerable adults in medical research may fail.…”
Section: Introductionmentioning
confidence: 99%